Postcolonial Erotic Disruptions: Legal Narratives of Culture, Sex, and Nation in India - Kapur, Ratna (Columbia Journal of Gender and Law, 2001)
In a recent diasporic production called “Fire,” the film’s director Deepa Mehta represents the dilemma of culture and authenticity that I seek to voice through this paper. The story involves the attraction between two rather stunningly beautiful women, Radha and Sita, who live together in a joint family household ruled by the bell of their mute mother-in-law. Their husbands are involved in other pursuits- whether it be celibacy for the purpose of finding spiritual salvation, or a sexual relationship with another woman who happens to be Chinese. Radha and Sita, whose names are the repositories of Indian cultural values in ancient texts and scriptures, are reimagined in the contemporary moment to transgress nearly every sexual, familial and cultural norm that constitutes India as it is imagined. The two women’s appropriation of rituals such as kharvachauth, a fast kept by wives to secure the longevity of their husbands, constitutes a celebratory moment when they trespass into an “unacceptable” sexual space. This moment culminates in what one reviewer curiously described as “the Indian lesbian scene.” But the women are not damned into the sexual exile of a “decadent West.” Instead, they are legitimated through another cultural move, the testing of a woman’s purity through the angnipariksha, the Fire that redeemed the original Sita from the wrath and condemnation of her husband Lord Ram and her community. Culture is invoked to counter culture. And this is where my story begins. This article is located on the precipice of desire and subversion. It is a story about normative sexuality in India and the ways in which it is inbred with an exclusionary narrative about culture, a narrative that is Hindu, unitary and fixed. It is also a story about how sexual speech and the performance of the sexual subaltern in law can serve as transgressive spaces of desire and pleasure. I examine specific legal controversies in the area of sexual speech, and the legal rights of the sexual subaltern, namely sex workers and gays and lesbians. These legal stories about sexuality are crossbred with stories about culture, producing their own hybridized offspring. I examine the spaces created by hybrid fantasies in law and how these spaces unhinge stoic and monotonous tales about sexuality and culture, and challenge dominant sexual ideology and exclusionary stories about culture.